2012
DOI: 10.1039/c2mb25172h
|View full text |Cite
|
Sign up to set email alerts
|

The serum metabolomic study of intervention effects of the traditional Chinese medicine Shexiang Baoxin Pill and a multi-component medicine polypill in the treatment of myocardial infarction in rats

Abstract: A metabolomic approach based on liquid chromatography coupled with quadrupole time-of-flight detector (LC-Q-TOF/MS) was developed to investigate the therapeutic mechanism of a traditional Chinese medicine (TCM) formula Shexiang Baoxin Pill (SBP) and a multi-component medicine polypill (consisting of simvastatin (Sim), atenolol (Ate), ramipril (Ram), hydrochlorthiazide (Hyd) and aspirin (Asp), named as SARHA). Twenty-seven biomarkers were identified in the serum of MI rats. Thirteen related pathways and 4 main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The decreased expression of Bax protein and the increased expression of Bcl-2 inhibit apoptosis, both contributing to reserve cardiac function. The activation of the phosphatidylinositol 3-kinase (PI3K) signaling pathway, including protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS) phosphorylation promote the synthesis of nitric oxide (NO), which is considered to be involved in the protection of endothelial function (16,23–25). …”
Section: Introductionmentioning
confidence: 99%
“…The decreased expression of Bax protein and the increased expression of Bcl-2 inhibit apoptosis, both contributing to reserve cardiac function. The activation of the phosphatidylinositol 3-kinase (PI3K) signaling pathway, including protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS) phosphorylation promote the synthesis of nitric oxide (NO), which is considered to be involved in the protection of endothelial function (16,23–25). …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the relevance between myocardial ATP exhaustion and the increased hypoxanthine and uridine has been clearly observed [39]; in addition, uridine has been considered a marker of myocardial viability after coronary occlusion and reperfusion and an indirect indicator of tissue energy crisis [40]. Increased uridine and decreased hypoxanthine were found in previous metabonomics study of myocardial infarction in rats [31, 41]; however, both hypoxanthine and uridine downregulated in our study and drug medication possibly play a role. On the other hand, when hypoxanthine converts to xanthine, reactive oxygen species (ROS) generate which is the characteristic of hypoxia and play a major role in microvascular dysfunction and exert direct tissue damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies have shown that SXJXDP contains numerous types of compounds, such as borneol and isoborneol from Borneolum, lactones (ligustilide and n-butylphthalide) and organic acids (ferulic acid) from Rhizoma Chuanxiong (2,3). Pharmacological studies have also revealed that major active components, including borneol, isoborneol, ligustilide, n-butylphthalide and ferulic acid, are implicated in the treatment of cardiovascular and cerebrovascular diseases (4)(5)(6)(7). Therefore, an efficient method should be developed to detect these compounds absorbed in the buccal mucosa.…”
Section: Introductionmentioning
confidence: 97%